Penggunaan Metode NaÃ¯ve Bayes untuk Memprediksi Tingkat Kemenangan pada Game Mobile Legends - Susilo, Ahmad Thoriq; Setiawan, Hendra; Saputro, Rizal Aji; Purwadi, Tirto; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2021)
The research conducted aims to predict the win or loss of a game in the Mobile Legend game. Because victory will greatly affect the level of play that is owned in the Mobile Legend game, and victory is also influenced by the player's ability to play the game and mastery of a game character that is used. The results of the study will show the results of the classification of the success rate of the method we use in predicting the success or victory of the game in the online game Mobile Legend which can be called the most popular game today. Many play this online game even from small children to adults. This game is very popular at this time, but there are still many who play while playing this game so that it greatly affects performance when doing battle games which results in many rankings dropping to the herro who doesn't move due to lag cellular network.